1992
DOI: 10.1128/mcb.12.10.4251
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of GT box-binding proteins: a novel Sp1 multigene family regulating T-cell receptor gene expression.

Abstract: Analysis of a T-cell antigen receptor (TCR) a promoter from a variable gene segment (V) revealed a critical GT box element which is also found in upstream regions of several Va genes, TCR enhancer, and regulatory elements of other genes. This element is necessary for TCR gene expression and binds several proteins. These GT box-binding proteins were identified as members of a novel Spl multigene family. Two regions (for reviews, see references 5 and 27). The process of V-D-J gene rearrangements is development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
384
0
5

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(406 citation statements)
references
References 40 publications
16
384
0
5
Order By: Relevance
“…These data indicate that the upper complex contains Spl, the lower complex may include an Spl-related protein. The formation of two major complexes with the Spl-binding site was also reported by others [20,21]. From the band intensities it appears that the nuclear extract from proliferating thymocytes yields more intense Spl bands (Fig.…”
Section: Resultssupporting
confidence: 82%
“…These data indicate that the upper complex contains Spl, the lower complex may include an Spl-related protein. The formation of two major complexes with the Spl-binding site was also reported by others [20,21]. From the band intensities it appears that the nuclear extract from proliferating thymocytes yields more intense Spl bands (Fig.…”
Section: Resultssupporting
confidence: 82%
“…We found that the human MIP gene sequence -253/+42 contains an active promoter in cultured lens cells but is inactive in non-lens cells (17). In the present study we have characterized a cis regulatory element required for MIP gene (18,19), is present in lens nuclear extracts and also interacts with this Sp1 binding site. Even though Sp1 is a ubiquitous factor, it regulates tissue-specific expression of a variety of genes (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 68%
“…However, as other members of the Sp family also interact with this motif (18,19) it was important to determine which member was involved in interaction with the CT box present at positions -55/-49 of the functional MIP promoter. When the oligonucleotide -67/-38 was incubated with mouse lens nuclear extract two retarded bands, C1 and C2, were observed (Fig.…”
Section: Differential Effect Of Sp1 and Sp3 Antibodies To Mip Gene Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferating cell nuclear antigen is an example of a protein originally identified as a human autoantigen that was later shown to have counterparts in many eukaryotic cells of different species (24). Anti-Spl autoimmune sera may be useful to search for Spl analogs in other species and to identify other human Spl-like proteins (27)(28)(29)(30). Some autoantibodies also recognize epitopes that are functionally important (24).…”
mentioning
confidence: 99%